1-Isobutyl-4-methoxy-1H-imidazo[4,5-c]quinoline - Fun, Hoong-Kun (International Union of Crystallography, 2011)
In the title compound, C(15)H(17)N(3)O, the 1H-imidazo[4,5-c]quinoline ring system is approximately planar, with a maximum deviation of 0.036 (1) Å. The C—N—C—C torsion angles formed between this ring system and the isobutyl unit are −99.77 (16) and 79.71 (17)°. In the crystal, intermolecular C—H⋯O hydrogen bonds link the molecules into chains along the c axis.